SPECIFIC FEATURES OF THE EFFECT OF ELECTRONIC BEAMS ON HARD ALLOY (Archive of Conferences, 2021)
A pulsed monoenergetic ion particle beam can also be used to inject energy into the surface layer of a target in a short time, and under suitable conditions, the surface layer can be melted. Ions lose energy as well as electrons on their way to the substrate. In this case, the released energy depends on the ion velocity, the atomic number of the target substance, and the mass of the incident particle.